THE INFLUENCE OF METABOLIC SYNDROME EDUCATION ON THE KNOWLEDGE LEVEL OF FEMALE STUDENTS USING POSTER, VIDEO, AND WORD SEARCH PUZZLE MEDIA AT SMPIT MENTARI ILMU KARAWANG - Khopiyani, Amalia; Kurniasari, Ratih (HEARTY, 2025)
In recent years, there have been many changes, one of which is the modern lifestyle. This lifestyle tends to be bad due to a lack of knowledge, which causes high levels of obesity-related diseases and has an impact on the occurrence of metabolic syndrome. The aim of this research is to determine whether or not there is an influence of poster media, educational videos, and random word puzzles on female students at SMPIT Mentari Ilmu Karawang. The type of research carried out was a quasi-experimental design with one group pre and post test to compare knowledge before and after being given a nutrition education media intervention. The sample used was 45 female student subjects. Data analysis using the Shapiro Wilk test, Wilcoxon test, and explanation in narrative form. The results of the research show an increase in nutritional knowledge in the three media from the results of the pre and post tests which were carried out with a p-value <0.05. Thus, this media can be used to facilitate young women in receiving nutritional information to prevent dangerous diseases, especially metabolic syndrome.